The effect of recurrent pulsed dye laser treatments in rosacea patients. (3rd April 2017) - Strand, Mark; Bergqvist, Gunnar; Griffith, Shane; Bergqvist, Emma
ABSTRACT: Background : Rosacea is common chronic skin condition and is known to have a negative impact on patient's quality of life. The use of pulsed dye laser treatment to improve quality of life is well documented in the literature. Prior work has emphasized a single series of laser treatments but we investigated the effect of recurrent pulsed dye laser treatment on patient's symptomatology and quality of life.Methods : We designed an 8 question survey about patient's rosacea symptoms, prior treatments, effectiveness of prior treatments, benefit of the laser treatments, and number of laser treatments. The survey (Figure 1) was offered to all patients over the age of 18 who were beginning or currently undergoing pulsed dye laser treatments who previously failed medical management for their erythematotelangiectatic rosacea.Results : Fifty patients completed the study. Patients had significant improvement in symptoms and show statistically significant benefit of repeated pulse dye laser treatment for rosacea versus a single series of treatments.Conclusion : Our study is unique in that it provides evidence that recurrent pulse dye laser treatments are beneficial to patients by improving quality of life and decreasing symptoms. This finding supports the notion that chronic treatment is needed for this chronic disease.